Chronic thromboembolic pulmonary hypertension mimicking coronary artery disease. (November 2020) - Correale, Michele; Fortunato, Martino; Magnesa, Michele; Varricchione, Giuseppe; Campanale, Giulio; Gravina, Matteo; Di Biase, Matteo; Daniele Brunetti, Natale
We report the case of 63-year-old man, complaining of dyspnea and with abnormal systolic motion of the interventricular septum at echocardiography, referred for coronary angiography and suspect coronary artery disease. In the presence of normal coronary angio, a specific work-up showed chronic thromboembolic pulmonary hypertension requiring pulmonary endarterectomy. The case highlights the need for a global cardiovascular and imaging approach in presence of poorly specific symptoms and signs of coronary artery disease.